2012
DOI: 10.1002/eji.201242394
|View full text |Cite
|
Sign up to set email alerts
|

Short‐term subcutaneous insulin treatment delays but does not prevent diabetes in NOD mice

Abstract: Despite encouraging results in the NOD mouse, type 1 diabetes prevention trials using subcutaneous insulin have been unsuccessful. To explain these discrepancies, 3-weekold NOD mice were treated for 7 weeks with subcutaneous insulin at two different doses: a high dose (0.5 U/mouse) used in previous mouse studies; and a low dose (0.005 U/mouse) equivalent to that used in human trials. Effects on insulitis and diabetes were monitored along with immune and metabolic modifications. Low-dose insulin did not have an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 37 publications
(63 reference statements)
1
14
0
Order By: Relevance
“…1% dose of INS used for intensive glycemic control in mice. This dose was selected in correspondence to the dose used in human trials and based on the dose used in insulin tolerance tests 44, 46, 47. We found that one-time injection of low-dose INS could transiently reduce hyperglycemia in T1D mice (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1% dose of INS used for intensive glycemic control in mice. This dose was selected in correspondence to the dose used in human trials and based on the dose used in insulin tolerance tests 44, 46, 47. We found that one-time injection of low-dose INS could transiently reduce hyperglycemia in T1D mice (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…INS glargine (Lantus; Sanofi-Aventis, France) was diluted in the buffer stated above. At D25, a single subcutaneous injection of INS glargine or equivalent buffer (Ctrl) was applied at 0.2-U/kg INS (about 0.004~0.005 U per mouse), corresponding to the dose used in human trials and based on the dose used in insulin tolerance tests 44, 46, 47. The INS dose was also adjusted to transiently restore euglycemia in diabetic mice based on our preliminary tests.…”
Section: Methodsmentioning
confidence: 99%
“…Only the high dose achieved some effects: it delayed but did not prevent diabetes onset, it reduced insulitis, and suppressed C-peptide secretion. However, all these effects were only transient and rapidly lost upon (83).…”
Section: Insulin In Clinical Trialsmentioning
confidence: 98%
“…For FcRn and vascular cell adhesion molecule (VCAM)-1 blocking experiments, PPI-Fc treatment was performed 24 h after intravenous injection of 100 mg IgG (rituximab) or anti-VCAM-1 mAb (clone M/K2.7, produced in-house). For transfer experiments, 15 3 10 6 splenocytes from the 14-week-old offspring of treated NOD mice were adoptively transferred into 4-to 6-week-old NOD.scid recipients and their pancreata were recovered for insulitis scoring as described (15). The study was approved by Comité d'Ethique pour l'Expérimentation Animale (P2.RM.117.09, CEEA34.SC.158.12).…”
Section: Surface Plasmon Resonancementioning
confidence: 99%